Outcome of Infants with Intracranial Tumors - J Gordon Millichap (Pediatric Neurology Briefs, 2012)
Investigators at British Columbia Children’s Hospital, Vancouver, Canada evaluated by retrospective chart review the long-term outcome and its predictors in all infants with a primary intracranial tumor seen at BCCH in the 23-year period, 1982-2005.